2009
DOI: 10.1093/pcp/pcp158
|View full text |Cite
|
Sign up to set email alerts
|

The Peptidoglycan Biosynthesis Genes MurA and MraY are Related to Chloroplast Division in the Moss Physcomitrella patens

Abstract: In the moss Physcomitrella patens, 10 Mur genes involved in peptidoglycan biosynthesis were found, and the MurE and Pbp genes are related to plastid division. Although the MraY and MurG genes were missing in our previous expressed sequence tag screening, they were discovered in the P. patens genome in this study, indicating that P. patens has a full set of genes capable of synthesizing peptidoglycan. In addition, a second MurA gene (PpMurA2) was found. Whereas Northern analyses indicated that PpMurA1, PpMurG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Disruption of the nucleus-encoded mur or mra genes impairs chloroplast division in the moss P. patens (Machida et al, 2006;Homi et al, 2009). The chloroplast genomes of certain green algal lineages still retain ftsI and ftsW genes.…”
Section: Chloroplasts In Glaucophytes and Intermediates Between Cyanomentioning
confidence: 99%
“…Disruption of the nucleus-encoded mur or mra genes impairs chloroplast division in the moss P. patens (Machida et al, 2006;Homi et al, 2009). The chloroplast genomes of certain green algal lineages still retain ftsI and ftsW genes.…”
Section: Chloroplasts In Glaucophytes and Intermediates Between Cyanomentioning
confidence: 99%
“…However, we and others have found that antibiotics that interfere with peptidoglycan biosynthesis can inhibit plastid division, generating giant chloroplasts, in the moss Physcomitrella patens (Kasten and Reski, 1997;Katayama et al, 2003). Due to progress in the P. patens genome-sequencing project, we were able to identify 10 homologs of Mur genes: MurA to G, MraY, penicillin binding protein (PBP), and D-Ala:D-Ala ligase (DDL), which are involved in biosynthesizing peptidoglycan (Machida et al, 2006;Homi et al, 2009). Disruption of the P. patens MurA, MurE, MraY, or Pbp resulted in the appearance of a smaller number of macrochloroplasts in each protonema cell, in contrast to wild-type plant cells, which have ;50 chloroplasts (Machida et al, 2006;Homi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Due to progress in the P. patens genome-sequencing project, we were able to identify 10 homologs of Mur genes: MurA to G, MraY, penicillin binding protein (PBP), and D-Ala:D-Ala ligase (DDL), which are involved in biosynthesizing peptidoglycan (Machida et al, 2006;Homi et al, 2009). Disruption of the P. patens MurA, MurE, MraY, or Pbp resulted in the appearance of a smaller number of macrochloroplasts in each protonema cell, in contrast to wild-type plant cells, which have ;50 chloroplasts (Machida et al, 2006;Homi et al, 2009). MurE mediates the formation of UDP-Nacetylmuramic acid (MurNAc)-tripeptide in bacteria ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…With the sequenced genome of moss (Rensing et al, 2008), genes for peptidoglycan biosynthesis pathway were discovered (Takano and Takechi, 2010). Knockout of PpPbp, PpMurE, PpMurA and PpMraY genes all showed a phenotype of enlarged chloroplasts (Machida et al, 2006;Homi et al, 2009), suggesting a role of chloroplast division of these genes. It needs to be further investigated whether the chloroplast in moss really has a peptidoglycan wall and whether this wall is related to chloroplast division if it does exist.…”
Section: Ftsimentioning
confidence: 99%